I Trust You Dr. Researcher, but not the Company that Handles My Data –Trust in the Data Economy - Rousi, Rebekah; Piispanen, Joni-Roy; Boutellier, Jani (University of Hawaii, 2024)
In the rising era of artificial intelligence (AI), learning machinery and hyper surveillance, trust is a sought-after attribute. The General Data Protection Regulation (GDPR) was introduced to increase individuals’ control over their own personal data, yet proof of its effectiveness is still lacking. Indeed, contrary to the intentions of the GDPR recent studies have shown numerous flaws in the regulation including issues from user negligence and ignorance to manipulation via dark design patterns etc. Even informed through the compulsory privacy notices and consent, people are experiencing less trust than ever. This is impacting every area of human society. This paper reports two interview studies (N=31) that probed individuals’ trust company-driven data handling practice and communication. The results demonstrate low to no trust in the perception of data-related information given by companies, rather perceiving researchers as trustworthy in terms of correspondence between data-handling related communication and the applied reality.
Keywords: Data Privacy; Communication; General Data Protection Regulation (GDPR); Business; Video Surveillance; trust; fi=Tietotekniikka|en=Computer Science|; fi=Viestintätieteet|en=Communication Studies|